Anti-atherogenic effects of fibrates in type 2 diabetes - Barter Philip (Current Controlled Trials in Cardiovascular Medicine, 2001)
Abstract Type 2 diabetes is an increasing cause of premature coronary heart disease. Several trials with lipid-modifying therapy have included sufficient numbers of diabetics to indicate that treatment of diabetic dyslipidaemia with either fibrates or statins reduces the risk of future coronary events in such patients. However, until recently no reported study had been designed specifically to investigate the effects of intervening in patients with type 2 diabetes. The Diabetes Atherosclerosis Intervention Study (DAIS) is an angiographic study in which 418 diabetic subjects were randomized to micronised fenofibrate or placebo groups. After 3 years of treatment, the fenofibrate group had a significantly reduced rate of progression of coronary atherosclerosis. This study, when considered with the results of other studies that have included diabetics, has important implications for the treatment of diabetic dyslipidaemia. The evidence that is currently available supports a place for both fibrates and statins, either as monotherapy or in combination, in the treatment of diabetic dyslipidaemia.